A expansão de mecanismos de participação nos anos 2000: as políticas públicas de juventude - Santos, Dayane Aparecida dos (2020)
The 2000s were marked by a series of transformations in the field of public policies in terms of focus, methods and objectives, accompanying a long trajectory of substantial social changes and political guidelines (these open with the inclusive and democratizing guidelines of the 1988 Federal Constitution). An example of this dynamic occurred with the implementation of participatory institutional arrangements that modified the relationship between the federal government and civil society, thus allowing the expansion of channels of dialogue and social control. These channels helped the inclusion of social groups in the sphere of political disputes and provoked a unique moment in the political history of the country, in which conferences, public consultations, plural arenas of discussion and deliberation expanded the protagonism of social groups and segments of civil society. In addition to innovation marked by close dialogue between state arenas and civil society, these arrangements express another form of public policy construction and a gap for the resignification of self-perception, identity and public image of social sectors such as youth (among others such as gender, race, indigenous people, traditional peoples, sexual orientation, etc.). This master's dissertation seeks to analyze the inclusion of the problems of youth (understood in the plural because of various historical forms of its definition and self-identification and also the plurality of intersections between various social markers such as gender, class, race, which perform it) in the decision-making agenda of the federal government from 2005. The National Youth Conferences are observed and the demands made explicit in them for the further development of youth public policies. Thus, the period analyzed corresponds to the context of the creation of the National Youth Secretariat and the National Youth Council and the three editions of the National Youth Conference (2008, 2011,2015). The period from 2005 to 2015 is a milestone. The central objective of the research was to understand how participatory institutional arrangements collaborated in the relationship between the federal government and the youth in developing public policies for this group. For this purpose, this dissertation contemplates various levels of analysis, linked to the change in political guidelines for public policies, the variation in the type and characteristics of public policies resulting from the expansion of the participatory democratic canon, the construction of new participatory institutional designs and, finally, possible gains in the agenda made possible by these arrangements with respect to the image and central demands of recent Brazilian youth. The work used as sources the documents resulting from the Conferences and publications of the Secretariat and National Youth Council, as well as secondary research on the profile of youth. The results obtained show that these participatory arrangements served to bring the youth closer to traditional political instances, as well as helping to absorb the main demands presented in subsequent actions by the executive and legislative branches.